Interferometria quântica com cavidades - Caio Olindo de Miranda Silva Junior (2006)
Using type I parametric down conversion, coincidence detection and the Hong-Ou-Mandel interferometer modified with the introduction of a Fabry-Perot cavity in one of its arms, we map the temporal distribution of the photon (one of those generated by the parametric down conversion), that pass through the cavity and we also measure the displacement of the peak of its temporal distribution after the cavity, in the photon longitudinal coherence length greater than the cavity length regime. We study the opposite regime, that is, where the cavity length is greater than the photon coherence length, and we found coalescence and anti-coalescence effects. The coincidence pattern, in this regime, is formed, in general, by peaks and dips which born from a constant value platform. The platform value depends only on the mirrors (that form the cavity) transmission and reflection coefficients, and it is proportional to the number of photons that cross the cavity. We complicated a little more, still in the cavity length greater than the photons coherence length regime, putting two cavities (each one in each of the interferometer arm), and we study the coincidence pattern for this case. The coincidence pattern is essentially the same of that found for the one cavity case. One of the main differences is that at this time the platform value depends also on the cavities lengths, and do not represents the number of the photons that cross the cavities anymore. We can simulate a C-NOT gate using this apparatus.Finally, using type II parametric down conversion, we study the case of two cavities which the transmission coefficients are polarization dependents. With this apparatus it is possible to distinguish conclusively the four Bell states: +, , _+ and _.